Smart Water Quality Surveillance System Using Iot-Based Remote-Controlled Boat (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Water pollution has become a major environmental concern due to rapid industrialization, urbanization, and agricultural activities. Traditional water quality monitoring methods are time-consuming and lack real-time capabilities. This paper presents an IoT-based smart water quality surveillance system using a remotely controlled boat integrated with sensors and wireless communication. The system utilizes an ESP32 microcontroller to measure parameters such as pH, turbidity, total dissolved solids (TDS), and temperature. The collected data is transmitted in real time to the Blynk IoT platform for remote monitoring and analysis. The boat can be navigated using a mobile application, enabling monitoring in remote and hazardous locations. The proposed system provides a cost-effective, efficient, and scalable solution for continuous water quality monitoring and environmental protection.